(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This work provides an overview of the role of rhythmic gymnastics in the physical education curriculum for school children. It discusses the fundamental principles and advantages of incorporating this form of physical activity into the educational process. The methods of conducting rhythmic gymnastics sessions are illuminated, encompassing technique, exercise examples, composition formation, and individualized approaches for students of varying skill levels. The paper also addresses the necessary set of knowledge and skills that a physical education teacher should possess for the successful execution of rhythmic gymnastics sessions. The author emphasizes the significance of this sport in the development of the physical, aesthetic, and social aspects of students’ personalities, as well as its influence on fostering an active lifestyle and healthy physical development.